1997
DOI: 10.1136/oem.54.9.671
|View full text |Cite
|
Sign up to set email alerts
|

Allergy risk in an enzyme producing plant: a retrospective follow up study.

Abstract: Objective-To investigate the risk of enzyme sensitisation and clinical allergy in workers exposed to enzymes at Novo Nordisk A/S. Methods-The study was a retrospective follow up study based on medical history and test data originally collected at routine screenings for enzyme allergy by the Occupational Health Service (OHS) of Novo Nordisk AMS during the period 1970-92. Workers were exposed to proteases, lipases, cellulases, and carboxyhydrases. Medical records of 3815 subjects were registered in the OHS datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
3
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 20 publications
0
34
3
1
Order By: Relevance
“…Some studies have reported that atopy is a risk factor of sensitization to enzymes [1,25], whereas others have concluded that it is not a significant risk factor [21,26]. In the present study, serum total IgE levels were found to be significantly associated with the presence of a powder allergy among exposed subjects, but no significant association was found between atopy and working duration in exposed medical personnel with an allergic reaction.…”
Section: Discussioncontrasting
confidence: 37%
“…Some studies have reported that atopy is a risk factor of sensitization to enzymes [1,25], whereas others have concluded that it is not a significant risk factor [21,26]. In the present study, serum total IgE levels were found to be significantly associated with the presence of a powder allergy among exposed subjects, but no significant association was found between atopy and working duration in exposed medical personnel with an allergic reaction.…”
Section: Discussioncontrasting
confidence: 37%
“…Hor v 17 (b-amylase) that 5% had work-related asthma and 3% rhino-conjunctivitis; IgE-mediated sensitisation mainly occurred to subtilisin, glycoamylase and/or trypsins (Johnsen et al 1997). Among 29 cooks in an industrial kitchen where a papain-containing meat-tenderiser was used, ten (34.5%) were sensitised and 50% reported respiratory and/or conjunctival hypersensitivity symptoms (Baur et al 1982).…”
Section: Purified Enzymes Causing Allergy In Industrial Workersmentioning
confidence: 98%
“…Many other high-molecular-weight allergens can induce IgE-mediated rhinitis and asthma: agricultural mites (339-342, 347, 348, 350, 351), coffee beans (598), proteolytic enzymes (515,599,600), other enzymes (601,602), insect dust (577); plants and flowers (603,604).…”
Section: Other Mitesmentioning
confidence: 99%